Preparation method and application of a highly wear-resistant mesoporous FCC catalyst

The preparation of high wear-resistant mesoporous FCC catalysts through a multi-step treatment method solves the problem of serious catalyst wear, significantly improves wear resistance and specific surface area, extends service life and improves industrial production efficiency.

CN119346145BActive Publication Date: 2025-03-21YUEYANG YITIAN CHEM
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411913376.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-21
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The existing FCC catalysts have severe wear due to mechanical stress during the fluidized bed catalysis process, which reduces the service life of the catalyst and industrial production efficiency.

Method used

A highly wear-resistant mesoporous FCC catalyst is prepared by a multi-step treatment method, including ammonium sulfate treatment, removal of non-branch aluminum, hafnium ion-substituted skeleton aluminum, polysorbate 80 treatment, vanadium nitrate treatment, magnesium polyphosphate treatment and polyamine treatment, through these steps, the catalyst's anti-wear properties and specific surface area are improved.

Benefits of technology

It significantly improves the wear resistance and specific surface area of ​​the catalyst microspheres, extends the service life of the catalyst, and improves the efficiency of the catalytic cracking process in petrochemical industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The first aspect of the present invention provides a highly wear-resistant mesoporous FCC catalyst, which improves the wear resistance of the FCC catalyst while maintaining the catalytic activity by systematically treating the catalytic core microspheres, the binder, the spray drying process and the surface of the catalyst microspheres; the second aspect of the present invention provides a method for preparing the highly wear-resistant mesoporous FCC catalyst; the third aspect of the present invention provides the application of the highly wear-resistant mesoporous FCC catalyst in petrochemical catalytic cracking.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of catalysts, and in particular to a preparation method and application of a highly wear-resistant mesoporous FCC catalyst. Background Art

[0002] Fluidized catalytic cracking (FCC) refers to the process used in petroleum refineries to convert high-boiling point, high-molecular-weight hydrocarbons of petroleum fractions into more valuable gasoline, olefin gas and other products. FCC catalyst refers to the catalytic material used in the fluidized bed catalytic process, which is mainly used to convert petroleum fractions into gasoline fractions. However, during the high-speed fluidization process, such as catalytic reaction, stripping, and regeneration cycle, the catalyst particles repeatedly rub and collide with each other and between the particles and the reactor wall, and the catalyst particles are subjected to huge mechanical stress in the entire circulation loop and wear. The wear mechanism is mainly divided into surface wear and bulk fracture. Generally, particles with low sphericity and rough surface are easily cut by airflow and undergo spherification process in fluidization to produce surface wear, while particles with poor bonding strength, many cracks, and loose and porous particles are easily broken after impact and collision and produce bulk fracture. Surface wear and bulk fracture usually exist simultaneously during the fluidization process of catalyst particles. Catalyst wear produces a large number of fine powder particles, which seriously reduces the service life of the catalyst and increases industrial production costs.

[0003] At present, the preparation process of FCC catalyst mainly includes the steps of slurry preparation, uniform mixing, spray granulation and high temperature calcination activation. In order to improve the wear resistance of catalyst particles, the research of existing technologies mainly focuses on the following aspects:

[0004] (1) Optimize the slurry preparation process, improve the overall mechanical strength of the catalyst particles, and reduce the bulk fracture and wear of the catalyst during fluidization;

[0005] (2) Optimize the spray forming process, improve the catalyst sphericity and particle size distribution uniformity, and further reduce the surface wear of the catalyst during the fluidization process.

[0006] Although industry researchers have made a lot of efforts, how to further improve the wear resistance of catalysts is still the focus of my country's FCC catalyst industry. Therefore, exploring how to improve the wear resistance of fluidized bed flower catalysts has important guiding significance for actual industrial production. Summary of the invention

[0007] In order to solve the above problems, the first aspect of the present invention provides a method for preparing a highly wear-resistant mesoporous FCC catalyst, comprising the following steps:

[0008] S1, ammonium sulfate treatment: dispersing the zeolite in an ammonium sulfate solution, washing, solid-liquid separation, drying, and calcining the zeolite to prepare zeolite I;

[0009] S2, removing non-framework aluminum: dispersing 1 part of zeolite I in water, adjusting the pH to 1.0 to 2.0 with oxalic acid; stirring the reaction for 1 to 3 hours;

[0010] S3, hafnium ion replaces framework aluminum: add hafnium oxalate to the solution of step S2, stir and react for 3 to 5 hours, filter and dry the zeolite to prepare catalytic core microspheres II; take catalytic core microspheres II, disperse them in water, use oxalic acid to adjust the pH to 1.0 to 2.0, and prepare suspension A;

[0011] S4, preparing a binder: taking a sodium-free silicate solution and a polyaluminium chloride solution, mixing them evenly to prepare a suspension B; the solute particle size in the sodium-free silicate solution does not exceed 5 nm; adding quasicrystal boehmite to the suspension B, adjusting the pH to 1.0-2.0 with oxalic acid, stirring and reacting for 3-5 hours to prepare a suspension C;

[0012] S5, polyamine treatment: adding polyamine to suspension C; stirring and reacting for 3 to 5 hours to prepare suspension D;

[0013] S6, magnesium polyphosphate treatment: adding magnesium polyphosphate to suspension D; stirring and reacting for 3 to 5 hours to prepare suspension E;

[0014] S7, vanadium nitrate treatment: adding vanadium nitrate to suspension E; stirring and reacting for 3 to 5 hours to prepare suspension F;

[0015] S8, polysorbate 80 treatment: add 0.01 to 0.03 parts of polysorbate 80 to suspension F; stir and react for 3 to 5 hours to prepare suspension G;

[0016] S9, binder-coated catalytic core microspheres: suspension A and suspension G are mixed, and stirred for reaction for 5 to 10 hours to obtain suspension H;

[0017] S10, primary drying and forming: spray drying the suspension H, and screening the dried particles to obtain microsphere catalyst III with a size of 40 um to 60 um;

[0018] S12, primary calcination: the microsphere catalyst III is calcined to prepare the microsphere catalyst IV;

[0019] S13, neodymium nitrate treatment: disperse the microsphere catalyst IV in water, add neodymium nitrate, and stir to react for 5 to 10 hours to prepare a suspension J;

[0020] S14, secondary drying: drying and dehydrating the suspension J to prepare a microsphere catalyst V;

[0021] S15, secondary calcination: the microsphere catalyst V is calcined to obtain a finished product.

[0022] As a preferred embodiment, the mass concentration of the ammonium sulfate solution is 30% to 50%.

[0023] As a preferred embodiment, in step S1, the mass ratio of zeolite to ammonium sulfate solution is 1:(3-5).

[0024] As a preferred solution, the calcination temperature in step S1 is 500° C. to 800° C., and the calcination time is 1 hour to 10 hours.

[0025] As a preferred solution, the drying temperature in step S1 is 100° C. to 180° C., and the drying time is 30 minutes to 60 minutes.

[0026] As a preferred embodiment, the reaction temperature of step S2 is 20°C to 25°C.

[0027] As a preferred embodiment, in step S2, the mass ratio of zeolite I to water is 1:(5-15).

[0028] As a preferred solution, the drying temperature in step S3 is 80°C to 180°C.

[0029] As a preferred embodiment, in step S3, the mass ratio of zeolite I to hafnium oxalate is 1:(0.01-0.03).

[0030] As a preferred embodiment, in step S3, the mass ratio of the catalytic core microsphere II to water is 1:(20-30).

[0031] As a preferred embodiment, in step S4, the mass ratio of the catalytic core microspheres II to the sodium-free silicate solution is 1:(2-4).

[0032] As a preferred embodiment, the mass concentration of the sodium-free silicic acid solution in step S4 is 30%.

[0033] As a preferred embodiment, in step S4, the mass ratio of the catalytic core microspheres II to the polyaluminium chloride solution is 1:(0.4-0.6).

[0034] As a preferred embodiment, the mass concentration of the polyaluminium chloride solution in step S4 is 60%.

[0035] As a preferred embodiment, in step S4, the mass ratio of the catalytic core microspheres II to the quasicrystal boehmite is 1:(0.1-0.2).

[0036] As a preferred embodiment, in step S5, the mass ratio of the catalytic core microspheres II to the polyamine is 1:(0.001-0.003).

[0037] As a preferred embodiment, in step S6, the mass ratio of the catalytic core microspheres II to magnesium polyphosphate is 1:(0.002-0.005).

[0038] As a preferred embodiment, in step S7, the mass ratio of the catalytic core microspheres II to vanadium nitrate is 1:(0.001-0.004).

[0039] As a preferred embodiment, in step S8, the mass ratio of the catalytic core microspheres II to polysorbate 80 is 1:(0.01-0.03).

[0040] As a preferred embodiment, in step S9, the mass ratio of the catalytic core microspheres II to polysorbate 80 is 1:(0.01-0.03).

[0041] As a preferred solution, the calcination temperature in step S12 is 550° C. to 600° C., and the calcination time is 2 hours to 4 hours.

[0042] As a preferred embodiment, in step S13, the mass ratio of the microsphere catalyst IV to water is 1:(10-20).

[0043] As a preferred embodiment, in step S13, the mass ratio of the microsphere catalyst IV to the neodymium nitrate is 1:(0.002-0.004).

[0044] The second aspect of the present invention provides a highly attrition-resistant mesoporous FCC catalyst, which is prepared by the above-mentioned preparation method.

[0045] The third aspect of the present invention provides the use of a highly attrition-resistant mesoporous FCC catalyst in petrochemical catalytic cracking.

[0046] Through the above technical solutions, the present invention produces the following technical effects:

[0047] (1) Through oxalic acid treatment, the non-framework aluminum in the zeolite is dissolved and removed, the catalyst stability and anti-wear performance are improved, and the specific surface area of ​​the zeolite is increased. Through ammonium sulfate treatment, NH4 + Replace sodium ions, and through high-temperature calcination, volatilize NH3 to form H-type zeolite, and the wear resistance is further improved. Through the treatment of neodymium nitrate, in the subsequent calcination process, neodymium forms an oxide form on the surface of the catalyst microspheres, which has high stability and improves the wear resistance. The presence of neodymium increases the strength of the acid site and improves its catalytic activity. Through the above treatment, the wear resistance of the catalytic core microspheres is improved.

[0048] (2) Through the treatment with polysorbate 80, the surface of the microparticles is made more rounded and the edges are reduced, thereby improving the wear resistance. In the subsequent high-temperature treatment process, polysorbate 80 volatilizes and decomposes, which can increase the specific surface area of ​​the microspheres and thus increase the activity index. Through the treatment with vanadium nitrate, in the subsequent calcination process, vanadium forms a VPO structure with phosphorus and oxygen, which has high stability and improves the wear resistance. At the same time, the presence of vanadium increases the strength of the acid site and improves its catalytic activity. Through the treatment with magnesium polyphosphate, in the subsequent calcination process, magnesium forms a spinel structure with aluminum and oxygen, which has high stability and improves the wear resistance. Phosphorus forms a PO-AL structure with aluminum and oxygen, which has high stability and improves the wear resistance. During the high-temperature treatment, magnesium polyphosphate decomposes and generates trace amounts of water that volatilizes, which can increase the specific surface area of ​​the microspheres and thus increase the activity index. Through the treatment with polyamine, cations such as H + 、Na + and Ca ++ Partially replaced by polyamine, this substitution reduces the negative charge on the clay microspheres, and the charge center near the end of the polymer chain reacts with the adjacent units and bridges, which enhances the bonding strength inside the microspheres, thereby improving the wear resistance. Sodium-free silica solution with a particle size not exceeding 5nm can easily enter the internal pores of the microspheres, form silica during the calcination process, and cover the surface of the microspheres. The wear resistance of the microspheres is improved by using the anti-wear properties of silica. Using sodium-free silica can avoid sodium ions with high solubility and improve the wear resistance of the catalyst. Through the above treatment of the binder, the wear resistance of the binder outside the core microspheres is improved.

[0049] (3) During spray drying, the pH value of the slurry is further away from the solute isopoint, and the mutual repulsion between particles of the same charge is utilized to reduce the probability of particle aggregation, reduce the particle size distribution, improve the uniformity of the solution, and improve the wear resistance. The above method treats the slurry and improves the wear resistance of the catalyst microspheres by controlling the spray drying process.

[0050] (4) After hafnium oxalate treatment, hafnium element is loaded on the inner surface of zeolite. During calcination, hafnium replaces the framework aluminum in zeolite to form a silicon-oxygen-hafnium structure, thereby improving the wear resistance. The above method can improve the wear resistance of the catalyst microsphere surface. DETAILED DESCRIPTION

[0051] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and understandable, the applicant first explains and analyzes through specific embodiments.

[0052] Example 1: S1, ammonium sulfate treatment: 1 part of zeolite is dispersed in 3 parts of ammonium sulfate solution with a mass concentration of 30%, and the zeolite is washed at 40°C for 1 hour; after solid-liquid separation, the zeolite is dried at 100°C for 30 minutes and calcined at 500°C for 1 hour to prepare zeolite I;

[0053] S2, removal of non-framework aluminum: disperse 1 part of zeolite I in 5 parts of water, adjust the pH to 1.0 with oxalic acid, maintain at 40°C, and stir for 1 hour;

[0054] S3, hafnium ion replaces framework aluminum: add hafnium oxalate to the solution of step S2 at a ratio of 0.01 part of hafnium oxalate to 1 part of zeolite I, stir and react at 20°C for 3 hours, filter and dry the zeolite at 80°C to prepare catalytic core microspheres II; take 1 part of catalytic core microspheres II, disperse it in 20 parts of water, adjust the pH to 1.0 with oxalic acid, and prepare suspension A;

[0055] S4, preparing a binder: taking 2 parts of a sodium-free silicate solution with a mass concentration of 30% and 0.4 parts of a polyaluminium chloride solution with a mass concentration of 60%, mixing them evenly to prepare a suspension B; the solute particle size in the sodium-free silicate solution does not exceed 5 nm; adding 0.1 parts of quasicrystal boehmite to the suspension B, adjusting the pH to 1.0 with oxalic acid, stirring and reacting for 3 hours to prepare a suspension C;

[0056] S5, polyamine treatment: add 0.001 parts of polyamine to suspension C, stir and react for 3 hours to prepare suspension D;

[0057] S6, magnesium polyphosphate treatment: add 0.002 parts of magnesium polyphosphate to suspension D, stir and react for 3 hours to prepare suspension E;

[0058] S7, vanadium nitrate treatment: add 0.001 parts of vanadium nitrate to suspension E; stir and react for 3 hours to prepare suspension F;

[0059] S8, polysorbate 80 treatment: add 0.01 parts of polysorbate 80 to suspension F; stir and react for 3 hours to prepare suspension G;

[0060] S9, binder-coated catalytic core microspheres: suspension A and suspension G are mixed, stirred and reacted for 5 hours to prepare suspension H;

[0061] S10, primary drying and forming: spray drying the suspension H, wherein the spray drying inlet temperature is between 300°C and the outlet temperature is between 105°C, and the dried particles are sieved to obtain microsphere catalyst III with a size of 40 microns;

[0062] S12, primary calcination: calcining the microsphere catalyst III at 550° C. for 2 hours to prepare the microsphere catalyst IV;

[0063] S13, neodymium nitrate treatment: 1 part of microsphere catalyst IV was dispersed in 10 parts of water, 0.002 parts of neodymium nitrate was added, and the mixture was stirred for 5 hours to prepare a suspension J;

[0064] S14, secondary drying: drying and dehydrating the suspension J to prepare a microsphere catalyst V;

[0065] S15, secondary calcination: the microsphere catalyst V is calcined at 550°C for 2 hours to obtain a finished product.

[0066] Example 2: S1, ammonium sulfate treatment: 1 part of zeolite was dispersed in 4 parts of ammonium sulfate solution with a mass concentration of 40%, and the zeolite was washed at 60°C for 1.5 hours; after solid-liquid separation, the zeolite was dried at 140°C for 45 minutes and calcined at 600°C for 5 hours to prepare zeolite I;

[0067] S2, removal of non-framework aluminum: Disperse 1 part of zeolite I in 10 parts of water, adjust the pH to 1.5 with oxalic acid; maintain at 70°C and stir for 2 hours;

[0068] S3, hafnium ion replaces framework aluminum: add hafnium oxalate to the solution of step S2 at a ratio of 0.02 parts of hafnium oxalate to 1 part of zeolite I, stir and react at 23°C for 4 hours, filter and dry the zeolite at 150°C to prepare catalytic core microspheres II; take 1 part of catalytic core microspheres II, disperse it in 25 parts of water, adjust the pH to 1.5 with oxalic acid, and prepare suspension A;

[0069] S4, preparing a binder: taking 3 parts of a sodium-free silicate solution with a mass concentration of 30% and 0.5 parts of a polyaluminium chloride solution with a mass concentration of 60%, mixing them evenly to prepare a suspension B; the solute particle size in the sodium-free silicate solution does not exceed 5 nanometers; adding 0.15 parts of quasicrystal boehmite to the suspension B, adjusting the pH to 1.5 with oxalic acid, stirring and reacting for 4 hours to prepare a suspension C;

[0070] S5, polyamine treatment: add 0.002 parts of polyamine to suspension C, stir and react for 4 hours to prepare suspension D;

[0071] S6, magnesium polyphosphate treatment: add 0.003 parts of magnesium polyphosphate to suspension D; stir and react for 4 hours to prepare suspension E;

[0072] S7, vanadium nitrate treatment: add 0.003 parts of vanadium nitrate to suspension E, stir and react for 4 hours to prepare suspension F;

[0073] S8, polysorbate 80 treatment: add 0.02 parts of polysorbate 80 to suspension F, stir and react for 4 hours to prepare suspension G;

[0074] S9, binder-coated catalytic core microspheres: suspension A and suspension G are mixed, stirred and reacted for 8 hours to prepare suspension H;

[0075] S10, primary drying and forming: spray drying the suspension H, wherein the spray drying inlet temperature is 500° C. and the outlet temperature is 150° C., and the dried particles are sieved to obtain 50 μm microsphere catalyst III;

[0076] S12, primary calcination: calcining the microsphere catalyst III at 580° C. for 3 hours to prepare the microsphere catalyst IV;

[0077] S13, neodymium nitrate treatment: 1 part of microsphere catalyst IV was dispersed in 15 parts of water, 0.003 parts of neodymium nitrate was added, and the mixture was stirred for 7 hours to prepare a suspension J;

[0078] S14, secondary drying: drying and dehydrating the suspension J to prepare a microsphere catalyst V;

[0079] S15, secondary calcination: the microsphere catalyst V is calcined at 580°C for 3 hours to obtain a finished product.

[0080] Example 3: S1, ammonium sulfate treatment: 1 part of zeolite is dispersed in 5 parts of ammonium sulfate solution with a mass concentration of 50%, and the zeolite is washed at 90°C for 2 hours; after solid-liquid separation, the zeolite is dried at 180°C for 60 minutes and calcined at 800°C for 10 hours to prepare zeolite I;

[0081] S2, removal of non-framework aluminum: Disperse 1 part of zeolite I in 15 parts of water, adjust the pH to 2.0 with oxalic acid; maintain at 95°C and stir for 3 hours;

[0082] S3, hafnium ion replaces framework aluminum: add hafnium oxalate to the solution of step S2 at a ratio of 0.03 parts of hafnium oxalate to 1 part of zeolite, stir and react at 25°C for 5 hours, filter and dry the zeolite at 180°C to prepare catalytic core microspheres II; take 1 part of catalytic core microspheres II, disperse it in 30 parts of water, adjust the pH to 2.0 with oxalic acid, and prepare suspension A;

[0083] S4, preparing a binder: taking 4 parts of a sodium-free silicate solution with a mass concentration of 30% and 0.6 parts of a polyaluminium chloride solution with a mass concentration of 60%, mixing them evenly to prepare a suspension B; the solute particle size in the sodium-free silicate solution does not exceed 5 nanometers; adding 0.2 parts of quasicrystal boehmite to the suspension B, adjusting the pH to 2.0 with oxalic acid, stirring and reacting for 5 hours to prepare a suspension C;

[0084] S5, polyamine treatment: add 0.003 parts of polyamine to suspension C and stir for 5 hours to prepare suspension D;

[0085] S6, magnesium polyphosphate treatment: add 0.005 parts of magnesium polyphosphate to suspension D, stir and react for 5 hours to prepare suspension E;

[0086] S7, vanadium nitrate treatment: add 0.004 parts of vanadium nitrate to suspension E, stir and react for 5 hours to prepare suspension F;

[0087] S8, polysorbate 80 treatment: add 0.03 parts of polysorbate 80 to suspension F, stir and react for 5 hours to prepare suspension G;

[0088] S9, binder-coated catalytic core microspheres: suspension A and suspension G are mixed, stirred and reacted for 10 hours to prepare suspension H;

[0089] S10, primary drying and forming: spray drying the suspension H, wherein the spray drying inlet temperature is between 600°C and the outlet temperature is 200°C, and the dried particles are sieved to obtain 60 um microsphere catalyst III;

[0090] S12, primary calcination: calcining the microsphere catalyst III at 600° C. for 4 hours to prepare the microsphere catalyst IV;

[0091] S13, neodymium nitrate treatment: 1 part of microsphere catalyst IV was dispersed in 20 parts of water, 0.004 parts of neodymium nitrate was added, and the mixture was stirred for 10 hours to prepare a suspension J;

[0092] S14, secondary drying: drying and dehydrating the suspension J to prepare a microsphere catalyst V;

[0093] S15, secondary calcination: the microsphere catalyst V is calcined at 600°C for 4 hours to obtain a finished product.

[0094] Example 4: In step S3, oxalic acid is used instead of hafnium oxalate, no hafnium ions are introduced, and no reaction of hafnium ions replacing framework aluminum is performed; other process parameters are consistent with Example 1.

[0095] Example 5: In step S3 and step S4, the pH of suspension A and suspension C is 6.5; other process parameters are consistent with Example 4.

[0096] Example 6: In step S4, sodium silicate is used instead of sodium-free silicic acid; other process parameters are consistent with those of Example 5.

[0097] Example 7: In step S4, the solute particle size in the sodium-free silicate solution is 10 nm; other process parameters are consistent with those in Example 5.

[0098] Example 8: The polyamine treatment in step S5 is omitted, and other process parameters are consistent with those in Example 7.

[0099] Example 9: The magnesium polyphosphate treatment in step S6 is omitted, and other process parameters are consistent with those in Example 8.

[0100] Example 10: The vanadium nitrate treatment in step S7 is omitted, and other process parameters are consistent with those in Example 9.

[0101] Example 11: The polysorbate 80 treatment in step S8 is omitted, and other process parameters are consistent with those in Example 10.

[0102] Example 12: There is no neodymium nitrate treatment in step S13, there are no steps S14 and S15, and other process parameters are consistent with Example 11.

[0103] Example 13: The ammonium sulfate treatment in step S1 is omitted, and other process parameters are consistent with those in Example 12.

[0104] Example 14: There is no step S2 of removing non-framework aluminum, and other process parameters are consistent with Example 13.

[0105] The light oil micro-reaction activity index of the microsphere catalysts prepared in Examples 1 to 14 was measured according to NB / SH / T0952-2017. The larger the index, the higher the activity.

[0106] The specific surface areas of the microsphere catalysts prepared in Examples 1 to 14 were measured using the Brunauer-Emmett-Teller (BET) method.

[0107] The wear index of the microsphere catalysts prepared in Examples 1 to 14 was measured according to ASTM D5757-95. The smaller the index, the higher the anti-wear performance.

[0108] The test results are shown in the table below. The following conclusions can be drawn from the table:

[0109] (1) Example 13 Compared with Example 14, Example 13 dissolves and removes non-framework aluminum, such as Al2O3, in the zeolite through acid treatment. Since non-framework aluminum is unstable and is more likely to fall off during fluidized reaction, the catalyst stability and anti-wear performance are improved after the non-framework aluminum is removed. While removing the non-framework aluminum, the specific surface area of ​​the zeolite is increased by acid erosion.

[0110] Al provides acidic centers in zeolite and plays a catalytic role. Removal of aluminum generally leads to a decrease in catalytic activity. The increase in specific surface area increases the catalytic activity, which offsets the decrease in catalytic activity caused by the reduction of aluminum.

[0111] (2) Compared with Example 13, Example 12 is treated with ammonium sulfate and ion exchange is performed to make NH4 + It replaces sodium ions and volatilizes N through high-temperature calcination to form H-type zeolite, which further improves the anti-wear performance.

[0112] (3) Compared with Example 12, Example 11 further improves the wear resistance through the treatment with neodymium nitrate. Neodymium is a rare earth element. During the subsequent calcination process, neodymium forms an oxide on the surface of the catalyst microspheres, which has high stability and improves the wear resistance. At the same time, the presence of neodymium increases the strength of the acid site and improves its catalytic activity.

[0113] (4) Compared with Example 11, Example 10 further improves the anti-wear performance by treating with polysorbate 80. Polysorbate 80 is a surfactant, and surfactant solutions have low surface tension and interfacial tension. After treatment with polysorbate 80, the surface of the microparticles becomes more rounded and the edges and corners are reduced during the spray drying process, thereby improving the anti-wear performance. In the subsequent high-temperature treatment process, polysorbate 80 volatilizes and decomposes, which can increase the specific surface area of ​​the microspheres and thus increase the activity index.

[0114] (5) Compared with Example 10, Example 9 further improves the anti-wear performance through the treatment of vanadium nitrate. Vanadium is a transition element. During the subsequent calcination process, vanadium, phosphorus and oxygen form a VPO structure with high stability, which improves the anti-wear performance. At the same time, the presence of vanadium increases the strength of the acid site and improves its catalytic activity.

[0115] (6) Compared with Example 9, Example 8 further improves the wear resistance of Example 8 through magnesium polyphosphate treatment. In the subsequent calcination process, magnesium forms a spinel structure with aluminum and oxygen, which has high stability and improves the wear resistance. Phosphorus forms a PO-AL structure with aluminum and oxygen, which has high stability and improves the wear resistance. In the subsequent high-temperature treatment process, magnesium polyphosphate decomposes and generates trace amounts of water volatilization, which can increase the specific surface area of ​​the microspheres and thus increase the activity index.

[0116] (7) Compared with Example 8, Example 7 further improves the anti-wear performance through polyamine treatment. The polyamine is characterized by a molecular weight of 50,000 to 500,000 Daltons, a high density of positive charges, and no anionic groups. + 、Na + and Ca ++ Partially substituted with polyamines, this substitution reduces the negative charge on the clay microspheres, and the charge center near the end of the polymer chain reacts and bridges with adjacent units, which strengthens the bonding strength inside the microspheres, thereby improving the anti-wear performance. Superfloc C577 is one of the commercially available polyamines.

[0117] (8) Compared with Example 5, Example 7 uses a sodium-free silica solution with a solute particle size of no more than 5 nm, which can easily enter the internal pores of the microspheres, and forms silica during the calcination process to form silica, which covers the surface of the microspheres. The anti-wear properties of silica are used to improve the wear resistance of the microspheres. When the solute particle size of the sodium-free silica solution is 10 nm, it is more difficult for the sodium-free silica to enter the pores, and it is impossible to form a silica coverage surface, so the wear resistance is low.

[0118] (9) Example 6 is compared with Example 5. Example 5 uses sodium-free silicate, while Example 6 uses sodium silicate. Since sodium ions have high solubility, they are easy to fall off during the use of the catalyst, resulting in reduced wear resistance of the catalyst.

[0119] (10) Compared with Example 4, in Example 5, the pH value of the slurry in Example 4 during spray drying is farther away from the solute isopoint, and the mutual repulsion between particles of the same charge is utilized to reduce the probability of particle aggregation, narrow the particle size distribution, improve the uniformity of the solution, and improve the wear resistance.

[0120] (11) Example 4 is compared with Example 1. Example 1 is treated with hafnium oxalate, while Example 4 is not treated with hafnium oxalate. Hafnium element is loaded on the inner surface of zeolite. During the calcination process, hafnium replaces the framework aluminum in zeolite to form a silicon-oxygen-hafnium structure, thereby improving the wear resistance.

[0121] The above results show that the preparation method of the present invention can significantly improve the anti-wear performance of the catalyst microspheres through multi-step system processing; at the same time, by increasing the specific surface area and increasing the acid center, the catalyst activity index is improved.

[0122] Table 1: Comparison of results of the examples

[0123]

[0124] The lattice constants of the catalysts prepared in Example 1, Example 2 and Example 3 were measured according to ASTM method D3942 to be 2.450 nm, 2.440 nm and 2.440 nm, respectively. When the lattice constant is less than 2.430 nm, the activity of the FCC catalyst composition may tend to be reduced.

[0125] The pore size distribution of the catalysts prepared in Example 1, Example 2 and Example 3 was measured by mercury intrusion porosimetry and was 5 nm to 10 nm.

Claims

1. A method for preparing a highly wear-resistant mesoporous FCC catalyst, characterized in that: The following steps are involved: S1, ammonium sulfate treatment: dispersing the zeolite in an ammonium sulfate solution, washing, solid-liquid separation, drying, and calcining the zeolite to prepare zeolite I; S2, removing non-framework aluminum: dispersing 1 part of zeolite I in water, adjusting the pH to 1.0-2.0 with oxalic acid; stirring the reaction for 1-3 hours; S3, hafnium ion replaces framework aluminum: add hafnium oxalate to the solution of step S2, stir and react for 3 to 5 hours, filter and dry the zeolite to prepare catalytic core microspheres II; take the catalytic core microspheres II and disperse them in water, use oxalic acid to adjust the pH to 1.0 to 2.0, and prepare a suspension A; S4, preparing a binder: taking a sodium-free silicate solution and a polyaluminium chloride solution, mixing them evenly to prepare a suspension B; the solute particle size in the sodium-free silicate solution does not exceed 5 nm; adding quasicrystal boehmite to the suspension B, adjusting the pH to 1.0-2.0 with oxalic acid, stirring and reacting for 3-5 hours to prepare a suspension C; S5, polyamine treatment: adding polyamine to suspension C; stirring and reacting for 3 to 5 hours to prepare suspension D; S6, magnesium polyphosphate treatment: adding magnesium polyphosphate to suspension D; stirring and reacting for 3 to 5 hours to prepare suspension E; S7, vanadium nitrate treatment: adding vanadium nitrate to suspension E; stirring and reacting for 3 to 5 hours to prepare suspension F; S8, polysorbate 80 treatment: add 0.01 to 0.03 parts of polysorbate 80 to suspension F; stir and react for 3 to 5 hours to prepare suspension G; S9, binder-coated catalytic core microspheres: suspension A and suspension G are mixed, and stirred for reaction for 5 to 10 hours to obtain suspension H; S10, primary drying and forming: spray drying the suspension H, and screening the dried particles to obtain microsphere catalyst III with a size of 40 μm to 60 μm; S11, primary calcination: the microsphere catalyst III is calcined to prepare the microsphere catalyst IV; S12, neodymium nitrate treatment: disperse the microsphere catalyst IV in water, add neodymium nitrate, and stir to react for 5 to 10 hours to prepare a suspension J; S13, secondary drying: drying and dehydrating the suspension J to prepare a microsphere catalyst V; S14, secondary calcination: the microsphere catalyst V is calcined to obtain a finished product.

2. The preparation method according to claim 1, characterized in that: The mass concentration of the ammonium sulfate solution is 30% to 50%, and the mass ratio of zeolite to the ammonium sulfate solution in step S1 is 1:(3-5).

3. The preparation method according to claim 2, characterized in that: The calcination temperature in step S1 is 500° C. to 800° C., and the calcination time is 1 hour to 10 hours. The drying temperature in step S1 is 100° C. to 180° C., and the drying time is 30 minutes to 60 minutes.

4. The preparation method according to claim 3, characterized in that: The reaction temperature of step S2 is 20°C to 25°C, and the mass ratio of zeolite I to water in step S2 is 1:(5-15).

5. A highly wear-resistant mesoporous FCC catalyst, characterized in that: The catalyst is prepared by the preparation method according to claim 1.

6. Use of the highly wear-resistant mesoporous FCC catalyst according to claim 5 in petrochemical catalytic cracking.

Citation Information

Patent Citations

  • Wear-resistant heavy oil catalytic cracking catalyst capable of reducing sulfur content of gasoline and preparation method thereof

    CN103028432A

  • Preparation method of catalyst for improving yield of diesel oil produced by catalytic cracking

    CN104275205A